2012
DOI: 10.1186/bcr3203
|View full text |Cite
|
Sign up to set email alerts
|

Invasive breast cancer induces laminin-332 upregulation and integrin β4 neoexpression in myofibroblasts to confer an anoikis-resistant phenotype during tissue remodeling

Abstract: IntroductionAlthough development of anoikis-resistant myofibroblasts during tissue remodeling is known to be associated with tumor invasion, the mechanism by which myofibroblasts become resistant to anoikis is unknown. We previously demonstrated laminin-332 upregulation in the fibrosis around invasive ductal carcinoma (IDC). Because laminin-332 promotes cell survival through binding to integrins, we hypothesized that invasive breast cancer cells confer an anoikis-resistant phenotype on myofibroblasts by upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…Strikingly, the top four pathways identified by gene-set enrichment analysis (GSEA) that are activated by exposure of tumor-promoting human fibroblasts to breast cancer cells are also amongst the top ten pathways activated in cultures of patient-derived breast carcinoma fibroblasts relative to normal fibroblasts (Figure 1). These pathways are ECM-receptor interaction, focal adhesion, integrin signaling and integrin cell-surface interactions; interrelated pathways that have been shown to be involved in the activation of cancer associated fibroblasts [21], [24], [25]. Additionally, most of the other top ten activated pathways in both systems were activated in the other system at lower ranking but still significant levels.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, the top four pathways identified by gene-set enrichment analysis (GSEA) that are activated by exposure of tumor-promoting human fibroblasts to breast cancer cells are also amongst the top ten pathways activated in cultures of patient-derived breast carcinoma fibroblasts relative to normal fibroblasts (Figure 1). These pathways are ECM-receptor interaction, focal adhesion, integrin signaling and integrin cell-surface interactions; interrelated pathways that have been shown to be involved in the activation of cancer associated fibroblasts [21], [24], [25]. Additionally, most of the other top ten activated pathways in both systems were activated in the other system at lower ranking but still significant levels.…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts are likely to be more restricted in their differentiation potential than multipotent MSCs, but they may retain some cellular plasticity which appears to be regulated by TGFβ. Very few studies have reported an anoikis-resistant phenotype of fibroblasts, however with a protective role of TGFβ on survival of differentiated fibroblasts [24, 25] which may be a distinct functional feature compared to assessing single-cell survival with subsequent sphere formation. Notably, CAFs appear to be associated with a loss in sphere-forming capacity potentially representing a more differentiated cell type with diminished regenerative ability or cellular plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…The predominance of LM-511 in advanced breast tumors however does not preclude a contribution by other LM isoforms during the early stage of tumor progression. For instance, the presence of LM-332-producing myofibroblasts at the tumor-stromal interface has been demonstrated in some invasive breast tumors 49 , 50 . LM-332 is expressed also in TN tumors 39 but it is not clear whether these represent a subset of breast cancer patients distinct from those with LM-511-expressing tumors.…”
Section: Lm-511 Expression In Normal and Cancer Tissuesmentioning
confidence: 99%
“…For example, downregulation of LM-511 and LM-332 occurring in cells undergoing EMT 78 , 79 may be necessary to decrease the strength of adhesion and facilitate the early acquisition of a mesenchymal phenotype. Cells migrating away from the primary tumor, could utilize myofibroblast-derived LM-332 at the tumor-stroma interface 50 . Conversely, re-expression of LM-511 at late stage of metastasis may provide the plasticity required for the reverse process of MET and facilitate the re-establishment of a proliferative epithelial phenotype at metastatic sites.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%